2010
DOI: 10.1037/a0020236
|View full text |Cite
|
Sign up to set email alerts
|

Mothers' teaching strategies and children's effortful control: A longitudinal study.

Abstract: Findings on the relation of maternal verbal teaching strategies to children's effortful control (EC; i.e., self-regulation) are limited in quantity and somewhat inconsistent. In this study, children's EC was assessed at 18, 30, and 42 months (ns = 255, 229, and 209, respectively) with adults' reports and a behavioral measure. Mothers' verbal teaching strategies were assessed while the mother and child worked on a task together. Children's general vocabulary also was measured. In a structural panel model taking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
83
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(93 citation statements)
references
References 73 publications
7
83
1
1
Order By: Relevance
“…Parents and teachers often use a ''tell-then-practice'' approach to teaching (Eisenberg et al, 2010;Hiebert et al, 2003;Roelofs, Visser, & Terwel, 2003). First children are told the important information, and then they are asked to practice using this information.…”
Section: Exploratory Activities and Improving Learning From Instructionmentioning
confidence: 96%
See 1 more Smart Citation
“…Parents and teachers often use a ''tell-then-practice'' approach to teaching (Eisenberg et al, 2010;Hiebert et al, 2003;Roelofs, Visser, & Terwel, 2003). First children are told the important information, and then they are asked to practice using this information.…”
Section: Exploratory Activities and Improving Learning From Instructionmentioning
confidence: 96%
“…This method helps children to quickly hone their attention to the most important information and, therefore, reduces the burden on cognitive resources (Bonawitz et al, 2011;Clark, 2009;Sweller et al, 1998). As a result, children spend less time on trial and error and reduce their use of erroneous beliefs or behaviors, instead practicing an appropriate way of thinking or acting in a domain (e.g., Eisenberg et al, 2010;Rittle-Johnson, 2006). Critically, without accurate instructional guidance, children often fail to discover correct information (e.g., Alfieri, Brooks, Aldrich, & Tenenbaum, 2011;Klahr & Nigram, 2004;Koenig & Woodward, 2010;Mayer, 2004).…”
Section: Exploratory Activities and Improving Learning From Instructionmentioning
confidence: 96%
“…Children's increasing behavioral regulation over the course of the early childhood period (between the ages of 2 years and 5 years) predicts a decline in parents' use of simple directives and an increase in teaching (Landry, Smith, Swank, & MillerLoncar, 2000). Parent teaching has been shown to provide support for children's autonomy, including cognitive and social independence, whereas directives appear to have a negative influence on autonomy development after the age of 3 years (Eisenberg et al, 2010). Although parents' RSA responses to stress have been linked with parental engagement with infants (e.g.…”
Section: Parent-child Coregulationmentioning
confidence: 99%
“…Gender differences are not always found; in fact, Matthews et al note that researchers have not often focused on such potential differences. However, when such differences have been tested, results favoring girls have been seen on both CEC tasks (Carlson & Moses, 2001) and HEC tasks (Clark, Sheffield, Wiebe, & Espy, 2013; Eisenberg et al, 2010; Li-Grining, 2007). Ponitz et al (2009) also found that girls achieved slightly higher behavioral self-regulation scores than boys.…”
Section: Ec and Child Characteristicsmentioning
confidence: 99%